Using timed and coloured Petri nets for modelling, simulation, and analysis of integration solutions. (28th February 2020) - Freddo, Francine; Sawicki, Sandro; Frantz, Rafael Z.; Roos-Frantz, Fabricia
Enterprise application integration (EAI) is a research field that seeks to develop methodologies, techniques and tools for the design and development of integration solutions. In this work, we propose to develop a mathematical model to simulate integration solutions in the design phase, i.e., before the implementation and testing stages. The aim of this simulation is to analyse the behaviour and identify the possible performance bottlenecks of the integration solutions. In this way, it is possible to identify problems prior to the implementation and testing stages. A conceptual model of the integration solution was translated into a mathematical model of the simulation using Petri nets. A real-life problem in the area of marketing was used as a case study. Finally, verification of the equivalence of the formal simulation model using timed and coloured Petri nets and the conceptual model, was performed using formal verification techniques widely found in the literature.